THE EFFECTIVENESS OF ROLE PLAY IN TEACHING SPEAKING - Lilis Suryani (STKIP Siliwangi, 2015)
Speaking is one of essential skills that should be mastered by students. In fact, the students face difficulties in speaking such as difficulty to arrange the sentences, fear of making mistakes, and lack of motivation. It is supported by Nunan (1993), he states that there are some challenges in teaching speaking skill in EFL classroom namely lack of motivation, and they tend to use their first language. Related to those problems, role play is offered to overcome the problems in speaking. The aim of the research was to know the effect of using role play in teaching speaking. The research used pre-experimental design with one group pre test and post test design which consist of 30 students as the sample. The data were obtained by using pre test and post test. Then, obtained data were analyzed by using SPSS 20. The result of the research showed that significance value was .00 and it is lower than the significance level .05. It means that the null hypothesis was rejected. Thus, teaching speaking by using role play has a significant effect on improving the students’ speaking ability. Keywords: role play, speaking, motivation